An Efficient Path Planning Algorithm Using a Potential Field for Ground Forces - Nakyeong Sung; Suhwan Kim; Namsuk Cho (Computation, 2023)
With the development and proliferation of unmanned weapons systems, path planning is becoming increasingly important. Existing path-planning algorithms mainly assume a well-known environment, and thus pre-planning is desirable, but the actual ground battlefield is uncertain, and numerous contingencies occur. In this study, we present a novel, efficient path-planning algorithm based on a potential field that quickly changes the path in a constantly changing environment. The potential field is composed of a set of functions representing enemy threats and a penalty term representing distance to the target area. We also introduce a new threat function using a multivariate skew-normal distribution that accurately expresses the enemy threat in ground combat.